Analisis Perbandingan Kinerja Keuangan Bank BUMN dan Bank BUMS Pada Sektor Perbankan yang Terdaftar di BEI Tahun 2020 – 2023 - Filka Maftikha; Nur Ainiyah; Muhammad Bahril Ilmiddaviq (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
This research aims to examine the differences in financial performance of state-owned banks and state-owned banks in terms of market value added ratios, liquidity ratios, solvency ratios, profitability ratios and activity ratios in the banking sector listed on the Indonesian stock exchange. The data analysis technique uses the Independent Sample t-test and uses a substitute test with the Mann-Whitney Test with SPSS (Statistical Product and Service Solutions) tools. The results of this research show that there is a significant difference between the financial performance of BUMN Banks and BUMS Banks seen from the Market Value Added Ratio, Liquidity Ratio, Solvency Ratio and Activity Ratio. On the other hand, there is no significant difference seen from the Profitability Ratio.